Tantangan dan Peluang Guru dalam Pembelajaran Abad 21: Studi Kasus Penguatan Literasi Digital Dalam Pembelajaran di MAN Sukoharjo - Dhesita, Syela Joe; Ihsani, Amelli Putri; Setyaningrum, Riris; Fitaloka, Chandra; Cahyono, Hery (Innovative: Journal Of Social Science Research, 2024)
21st century learning is characterized by critical thinking, creativity, communicative, adaptive, leadership and socio-cultural sensitivity. These various competencies must be possessed by the current generation amidst increasingly rapid advances in technology and information. So strengthening digital literacy is important to embed in the learning process to achieve student competency in 21st century learning. This article aims to photograph the problem of inappropriate use of technology in the learning process at MAN Sukoharjo and how teachers make efforts to strengthen digital literacy in the learning process. The research used a qualitative method with a case study approach which was carried out from July to October 2024. The research results showed that the problem in learning that emerged was the use of technology which could actually reduce students' real learning experiences and students' ability to think critically and be creative. Therefore, teachers at MAN Sukoharjo make various efforts to strengthen digital literacy in learning to create more contextual and meaningful learning for students. This is done as an effort to realize the challenges of 21st century learning.